Pharmacognostical Characterization and Evaluation of Invitro Antioxidant activity of Melia azedarach fruits - Chandra Tiwari, Girish; Prajapati, Manju (Journal of Neonatal Surgery, 2025)
Melia azedarach L, also known as Chinaberry tree, is a Southeast Asian plant with anti-inflammatory, antipyretic, analgesic, and insecticidal properties. It contains bioactive compounds like flavonoids, alkaloids, terpenoids, and saponins. Recent studies have shown that extracts from Melia azedarach L have anticancer properties and antimicrobial activity against various pathogens. Ayurveda, a traditional Indian medicinal system, has been practiced for thousands of years. Melia azedarach Linn, also known as mahanimba, is used for its anthelmintic, antilithic diuretic, emmenagogue, astringent, and stomachic properties. The tree is highly nutritious and has a calorific value of 5100 kcal/kg. It is also used in manufacturing agricultural implements, furniture, plywood, and fuel wood. In present study, pharmacognostical examination is done prior to its preclinical activity in order to check for its purity and having a record of possible phytochemicals present in the plants which may be responsible for its pharmacological action. Recent research on MEMA reveals its potent antioxidant capacity due to its high flavonoid content, which reduces damaging radicals. The presence of polyphenols in MEMA results in reduced oxidative stress indicators and increased protective capacity of antioxidants. This suggests that the methanol extract (MEMA) of Melia azedarach fruit has stronger antioxidant activity than the aqueous extract (AEMA), indicating its potential as a potential health supplement.